Local bearing empowerment towards smart society - Sihombing, Yuan Alfinsyah; Pasaribu, Nora Octavia; Aini, Nur Hizrah; Lumban Gaol, Al Trio Boy Beyto (Talenta Publisher, 2019)
Community Service Program (KKN) is a community service activity in certain areas as an implementation of the Tri Darma of Higher Education. Community service activities aim to provide field experience to students by assisting lecturers on the condition of the community directly and also to form an independent attitude and responsibility in carrying out community service activities. In addition, the service of KKN also aims to help the community in improving welfare. Community service activities are divided into three stages, namely preparation, implementation of activities on site, and evaluation. KKN educates students to continuously improve and maintain cooperation and a high level of social awareness to realize a work program that will be achieved. From this, students can increase their insight and experience that the success and success of a work program implementation is highly determined and influenced by good collaboration between fellow group members, supervisors and the local community. In this case we have proven that with good cooperation our work programs can be completed as expected.